Soil erosion risk assessment through morphometric indices for prioritization of watersheds in 7 northeastern region of India using multi-criteria analysis methods - Kumar Jena, Roomesh; CHANDRA MOHARANA, PRAVASH; SAHOO, SONALIKA; DASH, BENUKANTHA; KUMAR, NIRMAL; SHARMA, GULSHAN KUMAR; Ray, PRASENJIT; CHATTARAJ, SUDIPTA; SHARMA, R.P.; DEB ROY, PARTHA; P, SANDEEP; Das, BACHASPATI; et al. (Journal of Soil and Water Conservation, 2022)
Soil erosion has serious impact on socioeconomics, environment and agricultural production system. Soil erosion has been a prime concern for north-east India due to its hilly terrain, heavy rain fall and shifting cultivation. Morphometry along with land use land cover (LULC) information are essential aspects of watershed prioritization for soil erosion control as well as soil and water conservation. The present study intends to assess the soil erosion potential of Meghalaya plateau (Umsning) region of north-east India by analyzing different morphometry parameters along with existing land use land cover using multi-criteria analysis method. A total of 11 sub-watersheds (SW1 to SW11) were identified in the Umsning block using digital elevation model (DEM) and geographic information system (GIS) tools. Morphometric parameters affecting soil erosion along with LULC were used as criteria of ranking and compound values were obtained for final prioritization. Based on morphometric analysis, SW-1, SW-2, SW-3, SW-4 and SW-6 falls under extremely high priority group, whereas based on land cover only SW-1 falls under extremely high priority group. However, multi-criteria analysis combining both morphometry and LULC, suggest that the SW-1, SW-3 and SW-6 were falling under extremely high priority group while SW-7 was classified under very low priority. Planners and policy makers to develop integrated watershed management plan for socio-economic and environmental sustainability of the area can use the reported information.